Implementasi Good Corporate Governance Penguatan BUMN Dalam Perlindungan Keuangan Negara - Gusnia Gusnia; Etika Khairina; Timbul Dompak (Prosiding, 2023)
Promoting effective, open and compliant markets requires good governance. Therefore, in the current era of bureaucratic reform, the implementation of GCG in BUMN must be supported by 3 interrelated pillars, namely: The state and its systems act as regulators, businesses as market actors, and citizens as users of business products and services. Regulations issued by the government have a significant impact on the implementation of GCG. Society lends legitimacy to companies as providers of resources and buyers of company products. A good business leader must be able to balance different interests in supporting the business. This research method uses qualitative research, where these studies are systematized from several sections and phenomena and refer to causal relationships between theories from different sources.